Implementation of the ISM Code for MV Ships. Eastern Fair at PT Pelayaran Multi Jaya Samudera Belawan - Sonya Ledys Pakpahan; Fadiyah Hani Sabila (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
This paper aims to investigate the Implementation of the ISM Code on the MV Ships. Eastern Fair at PT. pelayaran Multi Jaya Samudera Belawan. In writing this paper, the author utilizes methodology, during the Onshore Practice, the author collects materials from field observation methods and library methods. This is intended to gain a deeper understanding of the Implementation of the ISM Code on the MV Eastern Fair Ship at PT. Pelayaran Multi Jaya Samudera Belawan. The ISM Code is an International regulation developed by the International Maritime Oeganization (IMO) to ensure the safety of ship operation and the protection of the marine environment. By integrating the principles of the ISM Code into their operations, shipping companies can create a safer and more efficient environment for both ship crew and onshore personnel. Safety onboard is a shared responsibility. Safety plays a crucial role in the overall operation of ships. Facts shw that as much as 80% of all accidents can be attributed to human error. Furthermore, about 75-80% of these human errors can be linked to poor management systems. Safety encompasses the ship, crew, cargo, and the marine environment. The Implementation of the ISM Code plays a crucial role in ensuring that everything runs smoothly in terms of safety.